Effect of non-genetic factors and estimation of heritability of lifetime traits in Sahiwal cattle - P. Kathiravan; G.K Sachdeva; R.S. Gandhi; P. K. Singh; T.V. Raja; K.N. Raja; S. Rajesh Kumar (Journal of Livestock Biodiversity, 2025)
The present study aimed to evaluate the influence of non-genetic factors and to estimate heritability of lifetime traits in Sahiwal cattle. Lifetime lactation records of 901 Sahiwal cows spread over a period of 33 years from 1973 to 2005, maintained at National Dairy Research Institute, Karnal and Government Livestock Farm, Chakganjaria, Lucknow were utilized. The mean total milk yield was significantly higher (P < 0.01) in Karnal herd compared to that of Lucknow herd in the first five lactations. The effect of season of calving had significant influence on total milk yield in second and fourth lactations of Sahiwal cattle. The effect of different periods of calving was significant (P